Autonomously Responsive Membranes for Chemical Warfare Protection. (27th April 2020) - Li, Yifan; Chen, Chiatai; Meshot, Eric R.; Buchsbaum, Steven F.; Herbert, Myles; Zhu, Rong; Kulikov, Oleg; McDonald, Ben; Bui, Ngoc T. N.; Jue, Melinda L.; Park, Sei Jin; Valdez, Carlos A.; et al.
Abstract: Stimuli‐responsive materials offer new opportunities to resolve long‐standing material challenges and are rapidly gaining pivotal roles in diverse applications. For example, smart protective garments that rapidly transport water vapor and autonomously block chemical threats are expected to enable an effective new paradigm of adaptive personal protection. However, the incorporation of these seemingly incompatible properties into a single responsive system remains elusive. Herein, a bistable membrane that can rapidly, selectively, and reversibly transition from a highly breathable state in a safe environment to a chemically protective state when exposed to organophosphate threats such as sarin is demonstrated. Dynamic response to chemical stimuli is achieved through the physical collapse of an ultrathin copolymer layer on the membrane surface, which efficiently gates transport through membrane pores composed of single‐walled carbon nanotubes (SWNTs). The adoption of nanometer‐wide SWNTs for ultrafast moisture conduction enables a simultaneous boost in size‐sieving selectivity and water‐vapor permeability by decreasing nanotube diameter, thereby overcoming the breathability/protection trade‐off that limits conventional membrane materials. Adaptive multifunctional membranes based on this platform greatly extend the active use of a protective garment and present exciting opportunities in many other areas including separation processes, sensing, and smart delivery. Abstract : A bistable membrane that rapidly and reversibly transitions from a highly breathable state to a chemically protective state when exposed to organophosphates is demonstrated. The threat‐triggered physical collapse of an ultrathin copolymer layer on the membrane surface efficiently gates transport through membrane pores made of single‐walled carbon nanotubes (SWNTs). The ultrafast moisture conduction of the SWNTs enables the overcoming of the breathability/protection trade‐off that limits conventional membrane materials.